EKSISTENSI PURA LANGGAR SEBAGAI ANALISIS PENDIDIKAN MULTIKUKTUR DI BALI - Paramita, Agung Agung Gde Krisna; Linda Dewi, Dewa Ayu Kade; Arsana, Dewa Nyoman (Widya Katambung, 2023)
Temple as a place of worship for Ida Sang Hyang Widhi Wasa is one of the ways to foster a sense of devotion and establish a relationship with God Almighty in the form of soul or niskala. The existence of God in the form of a soul and niskala needs to be manifested in the human mind because without that manifestation the human mind will not be directed and not steady enough to worship Him. Bali is an island of a thousand temples, one of which is a temple that has an existence in the era of globalization, namely Pura Langgar which is in Pakraman Bunutin Village, Bangli Regency, Bali Province. Pura Langgar is one of the characteristics of multicultural education in the religious life of Hindus and Muslims. Langgar Temple was formerly a Langgar, a place of prayer for Muslims. But the empress died, so a temple was built in that place with the name Pura Langgar. Where residing there is Ida Bhatara Pedanda Ratu. Because it is related to the Islamic religion, the ceremony does not use pork as a complement to the ceremony, but only ducks and chickens are sufficient.